Potential Utilization of Edible Insects as an Alternative Source of Protein in Animal Diets in Poland - Gałęcki, Remigiusz; Zielonka, Łukasz; Zasȩpa, Magdalena; Gołȩbiowska, Joanna; Bakuła, Tadeusz (Frontiers in Sustainable Food Systems, 2021)
The selection of high-protein raw materials that could be utilized in the production of animal feed is limited in Poland. The aim of this study was to analyze the needs and possibilities associated with the utilization of insect protein in animal nutrition in Poland. In the future, insects could become an effective solution to meeting the nutritional requirements of a growing population. Insect protein is already used in the production of fish feed in the European Union (EU). Legislative decisions on the introduction of this alternative feed source have to be based on the results of studies investigating the safety of insect protein for farmed animals. Diets containing insect protein and their influence on animals need to be thoroughly analyzed. In the future, insect farming could become a novel branch of agriculture, and it could create new opportunities for Polish farmers who were affected by the African swine fever (ASF) virus. Insect farms could create new jobs, promote innovative business development, and increase food and feed production. Entomophagy is a new and controversial concept for Polish consumers, but in the future, it could offer a viable solution to feeding the world’s growing population.